The efficacy of lactic acid bacteria-based toothpaste on oral health: a systematic review and meta-analysis - Choi, Eun-Mi; Park, Su-Kyung (Frontiers in Oral Health, 2025)
IntroductionLactic acid bacteria (LAB) have emerged as promising adjunctive agents for oral health management due to their antimicrobial and immunomodulatory properties. With the increasing incorporation of probiotics into oral care products, it is critical to evaluate their clinical efficacy. This systematic review and meta-analysis aimed to assess the effectiveness of LAB-based toothpaste in improving oral health outcomes.MethodsFollowing PRISMA guidelines, five databases (MEDLINE, EMBASE, Scopus, Web of Science, and CENTRAL) were searched through February 2025. Randomized controlled trials (RCTs) evaluating toothpastes containing probiotic, prebiotic, synbiotic, or postbiotic agents were included. Primary outcomes included plaque index (PI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment level (CAL). Secondary outcomes assessed oral microbiota changes. Risk of bias was evaluated using the RoB 2 tool.ResultsTwelve RCTs were included, with four studies suitable for meta-analysis. Meta-analysis demonstrated significant plaque reduction at 3 months [Mean Difference (MD) = −0.64; 95% confidence interval (CI): −1.14 to −0.15; p = 0.01] and BOP improvement (MD = −1.49; 95% CI: −2.42 to −0.56; p = 0.002). Longer interventions (≥6 months) in periodontitis patients revealed significant PPD reduction (MD = −1.32; 95% CI: −1.81 to −0.84; p < 0.00001) and CAL improvement (MD = −0.79; 95% CI: −1.25 to −0.33; p = 0.0007). Streptococcus mutans levels were significantly reduced across multiple studies.ConclusionsLAB-based toothpaste demonstrates beneficial effects on plaque control and gingival inflammation. However, substantial heterogeneity (I2 > 75% for most outcomes) limits effect estimate precision. Lactobacillus paracasei strains showed consistent benefits, while sustained use (≥6 months) appears necessary for periodontal improvements.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420250650340, PROSPERO CRD420250650340.